Long‐term alterations in monocyte function after elective cardiac surgery. (13th April 2017) - Zawadka, M.; Wahome, J.; Oszkiel, H.; Szeto, W. Y.; Cobb, B.; Laudanski, K.
Summary: Optimal immunological homoeostasis determines the long‐term recovery of patients in the postoperative period. The functional adaptability of monocytes plays a pivotal role in adjusting the host's response to an insult, immunostasis and long‐term health, and may help to determine successful recovery. We undertook a longitudinal analysis of the functional adaptability of monocytes in 20 patients undergoing heart surgery with cardiopulmonary bypass, as a model of severe stress. Using each patient's pre‐cardiopulmonary bypass data as a baseline, we investigated the characteristics of peripheral blood monocytes' functional plasticity in‐vitro before elective bypass, and three months afterwards. Approximately 30% of subjects showed diminished monocyte plasticity, as demonstrated by decreased monocyte differentiation into dendritic cells three months after bypass. Diminished monocyte functional plasticity was related to over‐production of macrophage colony‐stimulating factor. Adding a neutralising antibody to macrophage colony‐stimulating factor corrected the monocytes' differentiation defect. Finally, patients with reduced monocyte plasticity had significantly elevated serum C‐reactive protein, with a concomitant increase in cytomegalovirus IgG antibody titres, suggestive of the acquisition of immuno‐suppressive traits. Our study shows that severe surgical stress resulted in a lasting immunological defect in individuals who had seemingly recovered.